After the Earthquake in the Low-Altitude Economy, Drones Deliver Relief Supplies - Zhu, Xinyu; Chu, Jianyu (Scientific Journal of Technology, 2025)
The low-altitude economy is developing rapidly, and UAV post-earthquake rescue is helpful to improve the emergency response ability of post-earthquake rescue. Due to road damage, complex terrain, and uncertainty of meteorological conditions, ground rescue in the post-earthquake disaster area often cannot carry out full coverage of the earthquake-stricken area with high efficiency, while UAV has the characteristics of flexibility, dynamic real-time information, and intelligence, which is conducive to the application of post-earthquake rescue. The low-altitude economy has become a worldwide development trend, among which the development of low-altitude economy including UAM (UrbanAirMobility, urban air transportation), regional aviation logistics, and drones has become an important part of the global trend, and a variety of UAV application services and application scenarios such as logistics, environmental monitoring, and emergency rescue have been developed. Based on the background of low-altitude economic development, this paper discusses the application of UAV post-earthquake rescue, and analyzes the technical problems such as UAV post-earthquake rescue application technology, rescue material aerial throwing application, UAV route modeling airspace management application, etc., in order to play a positive role in post-earthquake rescue emergency response.